Ionoacoustic application of an optical hydrophone to detect proton beam range in water. Issue 4 (6th January 2023) - Sueyasu, Shota; Takayanagi, Taisuke; Miyazaki, Koichi; Kuriyama, Yasutoshi; Ishi, Yoshihiro; Uesugi, Tomonori; Unlu, Mehmet Burcin; Kudo, Nobuki; Chen, Ye; Kasamatsu, Koki; Fujii, Masayuki; Kobayashi, Masanori; et al.
Abstract: Background: Proton range uncertainty has been the main factor limiting the ability of proton therapy to concentrate doses to tumors to their full potential. Ionoacoustic (IA) range verification is an approach to reducing this uncertainty by detecting thermoacoustic waves emitted from an irradiated volume immediately following a pulsed proton beam delivery; however, the signal weakness has been an obstacle to its clinical application. To increase the signal‐to‐noise ratio (SNR) with the conventional piezoelectric hydrophone (PH), the detector‐sensitive volume needs to be large, but it could narrow the range of available beam angles and disturb real‐time images obtained during beam delivery. Purpose: To prevent this issue, we investigated a millimeter‐sized optical hydrophone (OH) that exploits the laser interferometric principle. For two types of IA waves [γ‐wave emitted from the Bragg peak (BP) and a spherical IA wave with resonant frequency (SPIRE) emitted from the gold fiducial marker (GM)], comparisons were made with PH in terms of waveforms, SNR, range detection accuracy, and signal intensity robustness against the small detector misalignment, particularly for SPIRE. Methods: A 100‐MeV proton beam with a 27 ns pulse width and 4 mm beam size was produced using a fixed‐field alternating gradient accelerator and was irradiated to the water phantom. The GM was set on the beam's central axis. Acrylic plates of various thicknesses, up to 12 mm, were set in front of the phantoms to shift the proton range. OH was set distal and lateral to the beam, and the range was estimated using the time‐of‐flight method for γ‐wave and by comparing with the calibration data (SPIRE intensity versus the distance between the GM and BP) derived from an IA wave transport simulation for SPIRE. The BP dose per pulse was 0.5–0.6 Gy. To measure the variation in SPIRE amplitude against the hydrophone misalignment, the hydrophone was shifted by ± 2 mm at a maximum in lateral directions. Results: Despite its small size, OH could detect γ‐wave with a higher SNR than the conventional PH (diameter, 29 mm), and a single measurement was sufficient to detect the beam range with a submillimeter accuracy in water. In the SPIRE measurement, OH was far more robust against the detector misalignment than the focused PH (FPH) used in our previous study [5%/mm (OH) versus 80%/mm (FPH)], and the correlation between the measured SPIRE intensity and the distance between the GM and BP agreed well with the simulation results. However, the OH sensitivity was lower than the FPH sensitivity, and about 5.6‐Gy dose was required to decrease the intensity variation among measurements to less than 10%. Conclusion: The miniature OH was found to detect weak IA signals produced by proton beams with a BP dose used in hypofractionated regimens. The OH sensitivity improvement at the MHz regime is worth exploring as the next step.